Pembibitan Jarak Pagar (Jatropha Curcas L. ) pada Jenis Tanah dan Penambahan Kompos yang Berbeda - Prihastanti, Erma (BULETIN ANATOMI DAN FISIOLOGI dh SELLULA, 2010)
Jatropha (Jatropha curcas L.) is one of the important crop for biofuel industry development and have the nature of drought tolerance that can be cultivated in marginal areas. One of cultivation technology that determines the success of planting jatropha seedlings in the field is the provision of plant nurseries in general use media that is around, such as soil and organic fertilizer. This study aims to observe the growth of jatropha seedlings on soil type and the addition of compost that is different from studies on the growth of leaves and roots. The results showed jatropha plant seedlings grown on soil rendzina, grumosol and regosol given compost or not for two months was able to grow and show the same increase in the number of leaves, wet weight and length of plant roots.